RELATIVE ABUNDANCE OF SCIAENIDS ALONG ANDHRA-ORISSA COAST - Rao, T Appa (Indian Journal of Fisheries, 2011)
A variety of species of sciaenids are known to occur along the east and west coasts of India (Lai Mohan 1969) where these form one of the commonest of groups in the fish catches. From the west coast, Hefford (1949), Jayaraman et al (1959) and Rao (1965) have dealt with the distribution, relative abundance and catch trends of ’ghol’ (Pseudosciaena diacanthus). Along the east coast, knowledge regarding the distribution and abundance of sciaenids is lacking. They contribute 10-15% of the total catches in the Government of India trawlers operated from Visakhapatnam. Studies on the distribution of sciaenids, occurring along the Andhra and Orissa coasts were taken up by the author and the present paper reports the results of investigations carried out on the basis of the data of M.T. Ashok during the period from 1964 to 1970 and of M.V. Champa during 1964-1971.